Pengaruh suhu pengeringan dan fortifikasi sari belimbing wuluh (Averrhoa bilimbi) terhadap karakteristik fruit leather buah carica (Pubescens lenne): The effect of drying temperature and fortification of bilimbi juice (Averrhoa bilimbi) on the characteristic of carica fruit leather (Pubescens lenne) - Cahyaning Rini Utami; Fitriani, Alisatul (Program Studi Ilmu dan Teknologi Pangan, Universitas Yudharta, Pasuruan, 2025)
Fruit leather is a processed fruit product in the form of thin, slightly plastic sheets produced from fruit puree or juice through a drying process. The fortification of bilimbi juice (Averrhoa bilimbi) in this fruit leather functions as an acidity regulator to replace citric acid. It is necessary to pay attention to the drying temperature for fruit leather products so that the nutrition of the fruit raw materials used to make fruit leather does not change much. This research aims to determine the effect of drying temperature and fortification of bilimbi juice on the characteristics of carica fruit leather (Pubescens lenne). This research method uses a Randomized Block Design consisting of two factors, namely differences in drying temperature and fortification of bilimbi. The first factor is the difference in drying temperature, namely S1: 50 ÌŠ C, S2: 60 ÌŠ C, and S3: 70 ÌŠ C. The second factor is fortification of bilimbi content of F1:10% bilimbi juice and F2: 12% bilimbi juice. The results of the calculation for the best treatment effectiveness index were found in S2F2 (temperature of 60Â°C + 12% bilimbi fortification or 30 ml). The physicochemical parameters of best treatment (S2F2) included antioxidant activity of 25.43%, tensile strength of 9.67 N, elasticity of 8.2%, water content of 0.46%, and ash content of 25.28%. The organoleptic parameters of best treatment were color at 3.48 (moderate), taste at 3.24 (moderate), and texture at 3.36 (moderate). Different drying temperatures (50, 60 and 70oC) with the fortification of bilimbi juice in Carica fruit leather has a significant effect on the parameters of antioxidant activity, tensile strength, elasticity, water content, ash content, and organoleptic tests which include color, taste, and texture.